2016
DOI: 10.1088/0741-3335/58/3/034014
|View full text |Cite
|
Sign up to set email alerts
|

Laser acceleration in argon clusters and gas media

Abstract: We experimentally investigated the generation of high-energy electron beams from laserdriven wakefield acceleration in argon gas jets by using tens of terawatt 30 fs ultrafast laser pulses that were focused to a relatively large-spot size, unmatched with the laser-plasma parameters. In this interaction, and depending on the Ar gas jet density, we could distinguish two different regimes for electron acceleration in the argon medium. In the high-density argon gas jet where argon clusters are formed, upon interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The mean charge measured on the electron spectrometer was 55 pC, with a standard deviation of 19 pC. The energy spectrum was continuous, as has been previously observed with cluster gas targets [30], but it also featured a peak of variable size and energy. By averaging over a burst of 50 shots, the quality of the data could be improved enough to be used with the optimization algorithm.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The mean charge measured on the electron spectrometer was 55 pC, with a standard deviation of 19 pC. The energy spectrum was continuous, as has been previously observed with cluster gas targets [30], but it also featured a peak of variable size and energy. By averaging over a burst of 50 shots, the quality of the data could be improved enough to be used with the optimization algorithm.…”
Section: Resultssupporting
confidence: 66%
“…However, the clusters make this extremely difficult, because they introduce physics on a length scale much smaller than the laser wavelength. We cannot neglect the clusters, as it has previously been shown that they substantially increase the amount of charge accelerated [22,30,43]. As such, these simulations are beyond the scope of this work.…”
Section: A Pulse Shapesmentioning
confidence: 99%
“…The nanoparticle insertion method for LWFA looks similar with the cluster target 31 , 32 where nano-scaled solids are mixed with a background gas. However, the acceleration mechanism is entirely different, where the either the dominant mechanism for acceleration is direct acceleration or the injection mechanism in LWFA is ionization injection.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental campaigns have looked at accelerated electrons from clustering gas targets (using methane and argon) discovering an impact on electron beam features due to the presence of clusters. These experiments observed a broader energy spectrum of the accelerated electron beam [43][44][45][46][47][48], increased amounts of accelerated charge [45,46], higher peak energies [45,46], and better reproducibility [47] using cluster targets. Researchers argued ( [43,45]) that a significant part of the acceleration of cluster electrons is due to direct laser acceleration (DLA).…”
Section: Introductionmentioning
confidence: 99%